2015
DOI: 10.4025/actascianimsci.v37i1.22830
|View full text |Cite
|
Sign up to set email alerts
|

<b>Effect of protease supplementation on production performance of laying hens

Abstract: The experiment was conducted with the objective of evaluating the effect of protease enzyme supplementation on performance parameters and quality shell of laying hens. We used 240 Isa Brown commercial laying hens with 44 weeks of age. A completely randomized split-plot design (5 periods of 21 days) with four treatments and six replications (10 hens per replication) was used. The experimental diets were formulated according to the requirements of the breed. The following parameters were evaluated: egg productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…Proteases increase the digestibility of proteins and amino acids, especially when the ingredients have low quality or low bioavailability (Kocher et al, 2002). Thus, besides providing nutritional benefits, the use of enzymes can contribute to the maintenance of the normal balance of the animal's organism, reflecting in better conditions for the performance and egg production (Vieira Filho et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Proteases increase the digestibility of proteins and amino acids, especially when the ingredients have low quality or low bioavailability (Kocher et al, 2002). Thus, besides providing nutritional benefits, the use of enzymes can contribute to the maintenance of the normal balance of the animal's organism, reflecting in better conditions for the performance and egg production (Vieira Filho et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Resende et al (2017) also found similar results, since they observed that the inclusion of an enzyme complex (β-glucanases, β-xylanases, cellulases, and phytases) at the dose of 50g/t in diets of Hy-Line Brown hens from 28 to 40 weeks old, provided improved rates for egg production, egg mass, conversion by dozen, and egg mass compared to hens fed diets with low nutritional density. Vieira Filho et al (2015) observed an increase in the laying rate by adding 500 g ton-1 of protease (100 Ug-1) to diets of Isa Brown commercial layers at 44 weeks old with reduced nutritional levels. Similarly, Silva et al (2012) observed a similar effect, reporting that birds fed diets with nutritional reduction and without supplementation of enzymes presented worse rates of feed conversion, confirming the positive effect of the inclusion of enzymes in diets of laying hens.…”
Section: Protease Supplementation In the Diet Of Light Laying Hensmentioning
confidence: 98%
“…На даному етапі деталізація технології вирощування здійснюється на високому рівні з врахуванням факторів, яким раніше вчені і практики не приділяли уваги. Наприклад, мікроструктурні зміни в кишечнику, зокрема, в слизових оболонках від яких залежить асиміляція нутрієнтів, стан і процеси які відбуваються у кишечнику визначають здоров'я птиці та ефективність використання поживних і біолого активних речовинах, що в свою чергу, пов'язано з інтенсивністю росту і розвитку, конверсією корму та іншими важливими господарськими показниками в птахівництві (Grozina, 2014;Filho et al, 2015;Dong et al, 2017). Відомо, що у птахівництві біля 70% собівартості продукції припадає на вартість кормів.…”
Section: вступunclassified